2016
DOI: 10.1016/j.compedu.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Student rules: Exploring patterns of students’ computer-efficacy and engagement with digital technologies in learning

Abstract: . (2016). Student rules: exploring patterns of students' computer-efficacy and engagement with digital technologies in learning. Computers and Education,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 63 publications
2
43
0
7
Order By: Relevance
“…Here, instruction-technology fit consists of the interplay between TDSTECH and TDSC, together explaining most of the variance in satisfaction (R 2 =0.765). Howard, Ma, and Yang (2016) using data mining on a very large dataset (N=8,817) found that computer self-efficacy was one of two main factors related to positive and negative engagement with digital technologies. The relevance of computer self-efficacy suggests that digital technologies used for learning have by no means become so intuitive and commonplace that the transactional distance relating to this, TDSTECH, has become irrelevant.…”
Section: Transactional Distance Of Student and Technologymentioning
confidence: 99%
“…Here, instruction-technology fit consists of the interplay between TDSTECH and TDSC, together explaining most of the variance in satisfaction (R 2 =0.765). Howard, Ma, and Yang (2016) using data mining on a very large dataset (N=8,817) found that computer self-efficacy was one of two main factors related to positive and negative engagement with digital technologies. The relevance of computer self-efficacy suggests that digital technologies used for learning have by no means become so intuitive and commonplace that the transactional distance relating to this, TDSTECH, has become irrelevant.…”
Section: Transactional Distance Of Student and Technologymentioning
confidence: 99%
“…In this paper, we focus on behaviors within the “group” task , possible social “group work” and resources as “digital technology integration” through an examination of key factors previously identified by Howard et al . () as important in students' experiences using digital technologies in learning (see Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Studying environmental effects when using digital technology provides a dynamic learning environment for teachers and students, as well as encourage the development of active students to use technology through innovative learning (Coll 2018;Blau & Shamir-Inbal 2018). The problem is that p-ISSN: 2461-0933 | e-ISSN: 2461-1433 133 e-Jurnal: http://doi.org/10.21009/1 the involvement of students in the use of technology in the learning process is still low (Howard, Ma & Yang 2016). It could be an excellent opportunity for teachers and students.…”
Section: Introductionmentioning
confidence: 99%